Host range and diversity of the genus Geosmithia (Ascomycota: Hypocreales) living in association with bark beetles in the Mediterranean area - Kolarík, Miroslav; Kostovcík, Martin; Pazoutová, Sylvie (Mycological research, 2007)
Geosmithia spp. (Ascomycota: Hypocreales) are dry-spored fungi that occur in galleries built by many phloeophagous bark beetles. This study mapped the diversity, host spectrum and area of distribution of Geosmithia spp. occurring in galleries of bark beetle species with a Mediterranean distribution. Eighty-six wood samples of 19 tree species infested by 18 subcortical insect species were collected from across the Mediterranean Basin during the years 2003-2006. Geosmithia spp. were found in 82 samples of angiosperms and two host trees from the family Juniperaceae infested by 14 bark beetles and the bostrichid Scobicia pustulata, suggesting that the association of Geosmithia and phloeophagous bark beetles is very widespread in the Mediterranean. Geosmithia isolates were sorted into 13 operational taxonomic units (OTUs) based on their phenotype similarity and phylogeny of their ITS regions of rDNA (ITS1-5.8S-ITS2). The OTUs represent five known species (G. flava, G. langdonii, G. lavendula, G. pallida, G. putterillii) and seven undescribed taxa. Most of the bark beetles were associated with on average 1-2.5 OTUs per sample. G. lavendula, considered very uncommon in nature, was found as a common associate of bark beetles. Six out of 13 OTUs were found to be distributed in the Mediterranean but not in neighbouring areas of temperate Europe suggesting that Geosmithia spp. have a geographically limited distribution, probably due to their dependency on the geographically limited area of their vectors. The proportion of generalists and specialists among Geosmithia spp. was smaller compared with data from temperate Europe. A possible explanation is the effective dispersal of Geosmithia by polyphagous bostrichids across the niches defined by mutually exclusive bark beetles.
Keywords: brouci; Phenotype; DNA fungální; Species Specificity; Coleoptera; sekvenční analýza DNA; Sequence Analysis, DNA; Plant Bark; DNA, Ribosomal Spacer; mezerníky ribozomální DNA; Animals; fenotyp; fylogeneze; cévnaté rostliny; molekulární sekvence - údaje; Hypocreales; zvířata; Mediterranean Region; Magnoliopsida; Tracheophyta; Molecular Sequence Data; Středomoří; kůra rostlin; DNA, Fungal; Phylogeny; technika náhodné amplifikace polymorfní DNA; druhová specificita; Random Amplified Polymorphic DNA Technique